gĜ-CLOSED SETS IN GRILL GENERALIZED TOPOLOGICAL SPACES - Anbarasan, R.; Anitha, M. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The aim of this paper is to introduce gĝ-closed sets in grill generalized topological spaces. Also, we investigate the properties of the μ‐gĝ-closed sets and discuss some characterization of μ-g-regular and μ-g-normal spaces.